PENERAPAN TOTAL QUALITY MANAGEMENT SEBAGAI UPAYA MEMPERKUAT DAYA SAING PERUSAHAAN - Irsatus Solehah; Maulidi Insan Kamil; Rahmatullah Ramadhani; Junaidi Efendi (PT. Hasba Edukasi Mandiri, 2026)
This research examines the effect of implementing Total Quality Management (TQM) on company competitiveness. The results show that TQM has a significant and positive effect on increasing competitiveness and company performance. Key contributing factors include customer focus, continuous system improvement, education and training, and employee involvement and empowerment. TQM improves various aspects of competitiveness such as operational efficiency, innovation, customer satisfaction, productivity and product quality. Effective strategies to overcome TQM implementation challenges include top management commitment, development of a quality culture, gradual implementation, effective communication, use of quality tools, continuous evaluation, and encouraging innovation. The research also discusses the impact of TQM on supply chain management and the importance of data-based decision making. In conclusion, effective TQM implementation can significantly increase a company's competitiveness in an increasingly competitive global market.